IDENTIFIKASI GUGUS FUNGSI DAN KANDUNGAN MINERAL LEMPUNG PACITAN DENGAN SPEKTROSKOPI INFRA RED (IR) X-RAY DIFFRACTION (XRD) - Pangoloan Soleman (LPPM Universitas Muhammadiyah Riau, 2011)
Clay is natural mineral from silicate family like crystal which has approximately 2 micrometer. There are two component unit of atom in clay mineral. One consists of oxygen or hidroksida with alumunium, iron or magnesium that coordinated in octahedral system. Others, it is tetrahedral system from silicon with oxygen or hidroksida. Based on IR analysis, it can be known that metal─OH bending vibrations it can be seen at 912,3 cm─1 wavelength. On the other bands between 694,3 and 754,1 cm─1 that are Si─O bending vibrations. X-Ray Diffraction (X-RD) analysis be seen main peak at 2 = 5,70o (d001=15,48 Å) and 2 = 20,02o (d001=4,43 Å). That are for smectite mineral kind montmorillonite as main unit in clay from Pacitan